Feniks . biuletyn informacyjny RKW NSZZ "Solidarność" Region Gorzów Wlkp., no. 101, 1985 - "Solidarność" (Agencja Wydawnicza "Feniks", 1985)
Creation and circulation: From issue no. 1=190(29.IV.1989) published legally